Associations between time-weighted personal air pollution exposure and amino acid metabolism in healthy adults. (November 2021) - Hu, Xinyan; Yan, Meilin; He, Linchen; Qiu, Xinghua; Zhang, Junfeng; Zhang, Yinping; Mo, Jinhan; Day, Drew B; Xiang, Jianbang; Gong, Jicheng
Graphical abstract: Highlights: Air pollutants may induce acute perturbation in amino acid metabolism profile. Short-term O3 exposure might induce perturbation of the urea cycle. Air pollution was associated with amino acids in relation to oxidative stress. O3 and PM2.5 may affect the amino acid metabolism in different pathways. Abstract: The molecular mechanisms underlying the associations between air pollution exposure and adverse cardiopulmonary effects remain to be better understood. Altered amino acid metabolism may plays an important role in the development of cardiopulmonary diseases and may be perturbed by air pollution exposure. To test this hypothesized molecular mechanism, we conducted an association analysis from an existing intervention study to examine the relations of air pollution exposures with amino acids in 43 Chinese healthy adults. Plasma levels of amino acids were measured using a UPLC-QqQ-MS system. Time-weighted personal exposure to O3, PM2.5, NO2, and SO2 over four time windows, i.e., 12 h, 24 h, 1 week, and 2 weeks, were calculated using the measured indoor and outdoor concentrations coupled with the time-activity data for each participant. Linear mixed-effects models were used to estimate the associations between air pollutants at each exposure window and amino acids by controlling for potential confounders. We observed significant associations between exposures and plasma concentrations of amino acids, with the direction of associations varying by amino acid and air pollutant. While there is little evidence of associations for NO2 and SO2, the associations with amino acids were fairly pronounced for exposure to PM2.5 and O3 . In particular, independent O3 (12- and 24-hour) associations were observed with changes in the amino acids that were related to the urea cycle, including aspartate, asparagine, glutamate, arginine, citrulline, and ornithine. Our findings indicated that air pollution may cause acute perturbation of amino acid metabolism, and that O3 and PM2.5 may affect the metabolism of amino acids in different pathways. Main finding : Acute air pollution exposure might affect the perturbation of amino acid metabolism, and in particular, was associated with amino acids in relation to the urea cycle.